Food Security in MENA Region - Al-Zu'bi, Maha (Hamad bin Khalifa University Press, 2023)
F2R-CWANA Initiative co-lead Maha Al-Zu'bi is a guest speaker on the Progress podcast and talks about how MENA nations are moving to bolster food security. The Progress podcast is created in both English and Arabic by the Program on Governance, Resilience, and Sustainability (PROGRESS) in the College of Public Policy and the College of Islamic Studies, both at Hamad Bin Khalifa University in Qatar.